2008
DOI: 10.1021/la8014145
|View full text |Cite
|
Sign up to set email alerts
|

Water/Supercritical CO2 Microemulsions with Mixed Surfactant Systems

Abstract: Phase behavior was investigated for water/supercritical CO 2 (W/scCO2) microemulsions stabilized with sodium bis(1H,1H,2H,2H-heptadecafluorodecyl)-2-sulfosuccinate (8FS(EO) 2) mixed with various guest surfactants. Only for the mixtures with fluorocarbon-hydrocarbon hybrid anionic surfactants (FC6-HC n), the maximum water-to-surfactant molar ratio (W0(c)) was larger than that estimated from linear interpolation of the W0(c) values for pure 8FS(EO) 2 and pure guest surfactant. Fourier transform infrared (FT-IR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
47
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 61 publications
1
47
0
Order By: Relevance
“…[3][4][5][6][7][8][9] However, most commercial and known hydrocarbon surfactants are insoluble and inactive in scCO2 systems 3 . In this regard, it became apparent that conventional surfactant-design theory cannot be applied to W/CO2 systems directly, and that CO2-philicity is not directly comparable to 4 oleo-philicity.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9] However, most commercial and known hydrocarbon surfactants are insoluble and inactive in scCO2 systems 3 . In this regard, it became apparent that conventional surfactant-design theory cannot be applied to W/CO2 systems directly, and that CO2-philicity is not directly comparable to 4 oleo-philicity.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, these surfactants are highly fluorinated and therefore expensive and environmentally unfriendly 25,26 . To overcome this problem, low fluorine/hydrocarbon replacements have recently been developed [27][28][29] .…”
Section: Introductionmentioning
confidence: 99%
“…However, only a few have succeeded in developing a W/scCO 2 mE with W 0 c > 0 (W 0 c :water-to-surfactant molar ratio corrected by subtracting the moles of water soluble in CO 2 ). In a previous work [20][21][22][23][24][25][26][27] , we synthesized fluorinated Aerosol-OT (AOT) analogue surfactants and examined their ability to stabilize W/scCO 2 mEs. We found that a fluorinated AOT-analogue surfactant, sodium bis(1H,1H,2H,2H-heptadecafluorodecyl)-2 -sulfosuccinate (8FS(EO) 2 ), successfully stabilized a transparent single-phase Winsor-IV W/scCO 2 mE (IV mE) with a W 0 c value of 32.…”
mentioning
confidence: 99%
“…The W 0 c value of 32 is extremely large compared to those previously reported for other W/scCO 2 mE systems . On the other hand, the IV mE became a turbid W/scCO 2 macroemulsion (E) with decreasing pressure, and then it turned into a Winsor-I-or Winsor-II-mE-like two-phase (2Ø) when magnetic stirring was stopped [20][21][22][23][24][25][26][27][28] . In this case, the Winsor-I and -II mean scCO 2 /W mE with a separated excess scCO 2 and W/scCO 2 mE with a separated excess water, respectively 28) .…”
mentioning
confidence: 99%
See 1 more Smart Citation